Tribuno de Roma - Fabbri, Robert (Fabbri, Robert. Vespasian series., 2012)
26 A.D. Sixteen-year-old Vespasian leaves his family farm for Rome, his sights set on finding a patron and following his brother into the army. But he discovers a city in turmoil and an Empire on the brink. With the situation in Rome deteriorating, Vespasian flees the city to take up his position as tribune in an unfashionable legion on the Balkan frontier. Unblooded and inexperienced, he must lead his men in savage battle with hostile mountain tribes - dangerous enough without renegade Praetorians and Imperial agents trying to kill him too. Somehow, he must survive long enough to uncover the identity of the traitors behind the growing revolt.